(التوزيع الجغرافي للخدمات السياحية في محافظة النجف الأشرف) (Journal of the College of Basic Education, 2026)
The Geographical Distribution of Tourism Services in Najaf Al-AshrafNajaf Al-Ashraf is one of the most important tourist destinations in Iraq, distinguished by its significant religious status and its many historical and natural sites that attract millions of visitors annually. This research aims to study the geographical distribution of tourism services in the governorate and assess their efficiency in meeting visitors’ needs while highlighting the gaps and challenges facing the tourism sector.The study adopts an analytical approach to examine the locations of hotels, restaurants, transportation, and other service facilities, using geographical maps to illustrate spatial distribution patterns. It also discusses the role of infrastructure in either enhancing or hindering tourism development and proposes solutions to improve the tourism sector, contributing to sustainable development in the governorate.The results indicate that most tourism services are concentrated in the city center and near the Shrine of Imam Ali (peace be upon him), while other areas suffer from a significant lack of facilities and services, affecting the distribution of tourist activity. The research recommends expanding the establishment of integrated tourism facilities in new areas and improving transportation networks and public services to support tourism throughout the governorate.